1988
DOI: 10.1016/s0006-3495(88)82933-3
|View full text |Cite
|
Sign up to set email alerts
|

Rotating-frame relaxation studies of slow motions in fluorinated phospholipid model membranes

Abstract: Rotating-frame relaxation experiments have been carried out on 19F-labeled dimyristoylphosphatidylcholine model membranes. The lipids are labeled with a single CF2 group in the 4-, 8-, or 12-position of the 2-acyl chain. Both oriented lipid bilayers and multilamellar liposomes have been investigated. The relaxation rate has been measured as a function of the locking-field strength, the sample orientation, the label position, and the temperature. Our results have confirmed that extensive slow motions exist in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Aside from those studies emphasizing lateral diffusion (9, 19), most existing models of the dynamics of phospholipids belong to one of two classes: (i) one or more noncollective anisotropic rotations of a lipid molecule (or a segment of the molecule) with well-defined correlation times (6-8, 10, 11, 16-18, 22); or (ii) collective bilayer disturbances with small angular modulations and a broad distribution of correlation times (13)(14)(15)20). Multiple motions coexist in a bilayer, even though different motions may have quite different geometries and time scales (20,21).Since most biochemical and biophysical processes occur on a microsecond or slower time scale, we believe that the slow motions of phospholipids (i.e., correlation time, r 2 10-6 sec) are more relevant to the function of biological membranes than their fast motions. Several studies have suggested that slow motions play an important role in lipidprotein interactions or lipid-mediated protein-protein interactions (4, 7, 14, 23).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Aside from those studies emphasizing lateral diffusion (9, 19), most existing models of the dynamics of phospholipids belong to one of two classes: (i) one or more noncollective anisotropic rotations of a lipid molecule (or a segment of the molecule) with well-defined correlation times (6-8, 10, 11, 16-18, 22); or (ii) collective bilayer disturbances with small angular modulations and a broad distribution of correlation times (13)(14)(15)20). Multiple motions coexist in a bilayer, even though different motions may have quite different geometries and time scales (20,21).Since most biochemical and biophysical processes occur on a microsecond or slower time scale, we believe that the slow motions of phospholipids (i.e., correlation time, r 2 10-6 sec) are more relevant to the function of biological membranes than their fast motions. Several studies have suggested that slow motions play an important role in lipidprotein interactions or lipid-mediated protein-protein interactions (4, 7, 14, 23).…”
mentioning
confidence: 99%
“…A number of nuclear magnetic resonance (NMR) investigations have focused on the molecular motions of phospholipids in a pure lipid bilayer, and various theoretical models have been proposed (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Aside from those studies emphasizing lateral diffusion (9,19), most existing models of the dynamics of phospholipids belong to one of two classes: (i) one or more noncollective anisotropic rotations of a lipid molecule (or a segment of the molecule) with well-defined correlation times (6-8, 10, 11, 16-18, 22); or (ii) collective bilayer disturbances with small angular modulations and a broad distribution of correlation times (13)(14)(15)20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 show the prediction for the case of a fixed headgroup tilt over the sample for two positions of the rotation axis. It is expected that in addition to the fast axially symmetric rotation there exist a rich array of slow motions of the lipid molecule as a whole and of various segments of the lipid macromolecule (17,(21)(22)(23). The effects of slower motions are included in this model by allowing the values of a and (# to vary over a specified range with equal weighting for simplicity.…”
Section: Modeling the Relaxationmentioning
confidence: 99%